2020
DOI: 10.1038/s41598-020-76015-3
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan overlaid Fe3O4/rGO nanocomposite for targeted drug delivery, imaging, and biomedical applications

Abstract: A hybrid and straightforward nanosystem that can be used simultaneously for cancer-targeted fluorescence imaging and targeted drug delivery in vitro was reported in this study. A chitosan (CS) polymer coated with reduced graphene oxide (rGO) and implanted with Fe3O4 nanoparticles was fabricated. The fundamental physicochemical properties were confirmed via FT-IR, XRD, FE-SEM, HR-TEM, XPS, and VSM analysis. The in vivo toxicity study in zebrafish showed that the nanocomposite was not toxic. The in vitro drug lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 52 publications
2
39
0
Order By: Relevance
“…CSNPs have been extensively used for bioactive compounds because of their high physicochemical stability, ability to enhance the bioavailability, non-toxicity, and potential targeted [ 16 ]. CSNPs are used as a diagnostic tool, targeted drug delivery, and a controlled delivery system [ 17 , 18 ]. CS modifications may be carried out using functional groups by various physical and chemical processes like grafting, crosslinking, complexation, and mixing with polymers [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…CSNPs have been extensively used for bioactive compounds because of their high physicochemical stability, ability to enhance the bioavailability, non-toxicity, and potential targeted [ 16 ]. CSNPs are used as a diagnostic tool, targeted drug delivery, and a controlled delivery system [ 17 , 18 ]. CS modifications may be carried out using functional groups by various physical and chemical processes like grafting, crosslinking, complexation, and mixing with polymers [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cytocompatible, a fluorescent and superparamagnetic nanocomposite consisting of CS-coated rGO and implanted with Fe 3 O 4 NPs achieving DOX loading of 0.448 mg/mL in vitro, was fabricated by Karthika et al [ 243 ] Surface modification of Fe 3 O 4 NPs with FA resulted in ameliorated uptake by A549 and MCF-7cancer cells and DOX release from this nanocomposite can be pH-triggered and controlled magnetically. Camptothecin ( Figure 3 )-loaded rGO decorated with magnetic NPs and cross-linked with a 4-hydroxycoumarin photosensitizer via an allylamine linker was found to be more toxic to MCF-7 cells than to normal fibroblast cell lines (WS-1).…”
Section: Graphene Oxidementioning
confidence: 99%
“…Promising transdermal delivery system based on ondansetron ( Figure 10) loaded Pluronic ® F127 stabilized rGO hydrogel (2% Carbopol ® 940 base) able to enhance the bioavailability and ensure sustained release of the drug used to manage vertigo, nausea and vomiting was developed by Li et al [241] Similarly, cyclosporine (a drug applied also in psoriasis treatment, Figure 14) incorporated in Pluronic ® F127 stabilized rGO hydrogel showed ameliorated permeation and retention, and the formulation was able to trap high amounts of the drug inside the skin tissue and reduced hyperplasia and tissue damage in psoriatic skin [242]. Cytocompatible, a fluorescent and superparamagnetic nanocomposite consisting of CS-coated rGO and implanted with Fe 3 O 4 NPs achieving DOX loading of 0.448 mg/mL in vitro, was fabricated by Karthika et al [243] Surface modification of Fe 3 O 4 NPs with FA resulted in ameliorated uptake by A549 and MCF-7cancer cells and DOX release from this nanocomposite can be pH-triggered and controlled magnetically. Camptothecin (Figure 3)loaded rGO decorated with magnetic NPs and cross-linked with a 4-hydroxycoumarin photosensitizer via an allylamine linker was found to be more toxic to MCF-7 cells than to normal fibroblast cell lines (WS-1).…”
Section: Go Used In Photoresponsive and Photothermal Therapymentioning
confidence: 99%
“…220 Furthermore, a new hybrid system was developed with a large loading capacity for cancer-targeted fluorescence imaging. 221 A nanocomposite made of chitosan, coated with graphene and Fe 3 O 4 nanoparticles (rGO/Fe 3 O 4 /CS) was used in vivo to determine their biocompatibility in zebrafish embryos. The study showed that the nanocomposites did not present any malformations and were less toxic in the specimen.…”
Section: Application Of Magnetic Chitosan In Cancer Diagnosismentioning
confidence: 99%